2020
DOI: 10.1123/ijspp.2019-0333
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Postexercise Sauna Bathing on Recovery of Swim Performance

Abstract: Purpose: Despite indications of positive effects of sauna (SAU) interventions, effects on performance recovery are unknown. The aim of the current study was to investigate acute effects of SAU bathing after an intensive training session on recovery of swim performance. Methods: In total, 20 competitive swimmers and triathletes (3 female and 17 male) with a minimum of 2 y of competition experience (nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…On the other hand, Skorski et al showed that three 8-min sessions of post-exercise sauna bathing at 80–85 °C had a detrimental effect on the swimmers’ times. The authors concluded that coaches should be mindful when choosing sauna bathing for post-exercise recovery [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Skorski et al showed that three 8-min sessions of post-exercise sauna bathing at 80–85 °C had a detrimental effect on the swimmers’ times. The authors concluded that coaches should be mindful when choosing sauna bathing for post-exercise recovery [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found positive acute cardiovascular responses from the use of passive heat ( 50 ), sauna exposure ( 27 , 51 ), and sauna exposure with exercise ( 52 , 53 ). A recent study also showed that postexercise sauna exposure had an augmentative effect, thereby increasing the overall training stress ( 54 ). However, to our best knowledge, this is the first multi-arm RCT investigating the cardiovascular and health effects of long-term sauna exposure in the general population with CVD risk factors.…”
Section: Discussionmentioning
confidence: 99%
“… 38 This is comparable to how exercise increases dilation of arteries supplying skeletal muscle, which has been documented to lead to reduced wave reflection. 39 The efficacy of heat stress from the sauna was inadvertently shown in a more recent study, 40 which sought to utilize the sauna as a post‐training recovery tool. Instead of providing a recuperative effect, performance measures were decreased.…”
Section: Discussionmentioning
confidence: 99%